25 anos da Lei de Tortura (1997-2022): sujeito ativo, prescrição e a proporcionalidade da pena sob a perspectiva do direito penal redutor - Lima, Vladimir Sampaio Soares de (2024)
This work conducts a critical analysis of the 1997 Brazilian Torture Law, focusing on the controversies surrounding the perpetrator, the statute of limitations, and the proportionality of penalties. From the perspective of Reductive Criminal Law, the research aims to identify and problematize gaps and inconsistencies in the legislation, proposing alternatives aimed at containing punitive power and effectively protecting human rights. Through a review of specialized literature and judicial decisions, the study questions the role of Criminal Law in responding to human rights violations, especially considering the predominant punitive discourse. It also analyzes the compatibility of the Torture Law with International Human Rights Law, with emphasis on the jurisprudence of the Inter-American Court of Human Rights on serious human rights violations. The research deepens the discussion on imprescriptibility, examining Brazilian legislation, national and international jurisprudence, and an innovative decision by the Federal Regional Court of the 3rd Region on the subject. Furthermore, the work analyzes all bills aimed at amending the Torture Law between 1997 and 2022, seeking to identify trends and proposals for legal reform. Additionally, it investigates the proportionality of penalties for the crime of torture, advocating a perspective of reducing punitive power and seeking a proposal that best fits the gravity of the crime, without exacerbating the suffering caused by the criminal justice system